Longitudinal impact of the Women's Health Initiative study on hormone therapy use in Australia. (3rd September 2019) - Natari, R. B.; McGuire, T. M.; Baker, P. J.; Clavarino, A. M.; Dingle, K. D.; Hollingworth, S. A.
Abstract: Purpose: This study aimed to examine the longitudinal impact of evidence changes on menopausal hormone therapy (MHT) use in Australia. Methods: We analyzed two datasets of subsidized and total MHT use (2000–2016) using segmented regression analysis to explore the impact of the Women's Health Initiative (WHI) 2002 and 2007 studies. Analyses were stratified by class, route, and strength. Use was measured in defined daily dose/1000 women/day (DDD/1000/day) or packs/1000 women/month (packs/1000/month). Results: The drop in total MHT use after the WHI 2002 was substantial. The biggest decreases in class, route, and strength were estrogens (28.99 DDD/1000/day, 95% confidence interval [CI] 23.97, 34.01), oral (46.07 DDD/1000/day, 95% CI 41.13, 51.01), and medium strength (34.95 packs/1000/month, 95% CI 30.17, 39.73), respectively. However, vaginal use remained stable (−1.83 DDD/1000/day, 95% CI −3.83, 0.17). Profiles of total and subsidized use were similar over time. Utilization levels were relatively unchanged after 2007. Decreased utilization contributed to product discontinuation, with a lag of up to 4 years. Product discontinuation in 2009 further decreased utilization. Discussion and conclusions: MHT use remained low after 2002 despite evidence favoring its use in women younger than 60 years or within 10 years postmenopause. Continued low use could relate to the WHI 2002 media coverage, therapy objectives, key stakeholder uncertainty, health policies, and medicine availability.